Retrospective medico-social analisys of the results of treatment patients with the concequences of long bone fractures - Tankut, Volodymyr; Golubeva, Inna; Rykun, Mykola; Berenov, Kostyantyn; Androsenkova, Viktoria (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2021)
The problem of long bones fractures treatment remains actual, despite a significant number of studies carried out on this topic. Such fractures of the musculoskeletal system occur more often and are accompanied by various complications, significantly compromise the quality of patients life and often lead to the disability. Objective. To analyze different types of traumatic injuries in patients with the consequences of long bone fractures, to evaluate the effectiveness of diagnostics, treatment and to analyze the state of disability. Methods. A retrospective medical and social analysis of the results of treatment of 333 patients (232 (69.6 %) men, 101 (30.4 %) women) with the consequences of long bone fractures, based on the obtained study group in the Kharkiv Regional Center for Medical and Social Expertise № 2, for the period 2018–2019. Results. Three main methods of surgical treatment were analyzed: internal fixation (ORIF), blocking intramedullary nailing (IMN) and treatment with external fixation devices (EF). They were applied in the following rate: ORIF — 204 (61.3 %) cases, IMN — 98 (29.4 %), EF — 31 (9.3 %). The most typical complications of the treatment of patients with fractures of the long bones were delayed union or nonunion, neuropathies of the treated extrimities, joint contractures, osteoarthritis of adjacent joints, deformities of affected extrimities, osteomyelitis. Causes of disability were: 63 % — severity of injuries, 46 % — different posttraumatic complications, 6.5 % — iatrogenic complications. Among the latter, the most common were: diagnostic — 7.1 %, incorrect method of treatment — 29.7 %, iatrogenic incorrect surgery methods — 45 %. Conclusions. The data obtained showed that the improvement of organization measures for the prevention of complications and disability in patients with consequences of long bones fractures could help to increase the efficiency and quality of specialized medical help. Key words. Fractures, long bones, limbs, consequences, complications, disability.